2014
DOI: 10.1371/journal.pone.0093952
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Morphology-Based Prediction of Multiple Differentiation Potentials of Human Mesenchymal Stem Cells for Early Evaluation of Intact Cells

Abstract: Precise quantification of cellular potential of stem cells, such as human bone marrow–derived mesenchymal stem cells (hBMSCs), is important for achieving stable and effective outcomes in clinical stem cell therapy. Here, we report a method for image-based prediction of the multiple differentiation potentials of hBMSCs. This method has four major advantages: (1) the cells used for potential prediction are fully intact, and therefore directly usable for clinical applications; (2) predictions of potentials are ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Previous methods of morphological assessment have relied exclusively on unsupervised PCA and other multivariate analyses . Although inclusion of all cell morphological features in an unsupervised PCA allows for an unbiased morphological signature assessment, this includes features with high degrees of variability and with potentially poor correlation with mineralization capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous methods of morphological assessment have relied exclusively on unsupervised PCA and other multivariate analyses . Although inclusion of all cell morphological features in an unsupervised PCA allows for an unbiased morphological signature assessment, this includes features with high degrees of variability and with potentially poor correlation with mineralization capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This group also showed how measuring cell morphological parameters can be used in combination with experimental data in order to predict stem cell phenotypic outcomes at a later time point. Here, stem cell shape was used as predictive marker with the intention to replace measuring later time points [21][22][23]. Hence, studies have begun to increasingly and successfully use quantitative approaches to access morphological parameters and to correlate them to biological parameters and cell fate outcome.…”
Section: Cell Morphology As a Novel Tool To Assess Biological Responsmentioning
confidence: 99%
“…As an example, using high content imaging, Marklein et al [25] demonstrated that nuclear morphological profiles of MSCs had distinct morphological features that were highly predictive of MSC mineralization capabilities, with >90% accuracy. Kato's group has proposed a similar theory [21][22][23]26]. Their group demonstrated that cell morphological features from the first three days of differentiation can predict osteogenic differentiation potential (i.e., alkaline phosphatase and calcium deposition).…”
Section: Cell Morphology As a Novel Tool To Assess Biological Responsmentioning
confidence: 99%
“…[6][7][8][9] We applied this technique to evaluate the quality of cultured cells, including the differentiation potential of stem cells. [3][4][5] Our morphologybased evaluation method provided not only the three aforementioned advantages but also enabled daily evaluation of rapidly changing cellular conditions. In this report, we verified the ability of our method to evaluate the cellular response to potential drug lead compounds.…”
Section: Research-article2016mentioning
confidence: 99%